E-cigarette use in Serbia: Prevalence, reasons for trying and perceptions. (April 2019) - Kilibarda, Biljana; Krstev, Srmena; Milovanovic, Minja; Foley, K.
Highlights: Curiosity is the main reason for trying e-cigarettes among Serbian adults. Perceived impact of e-cigarette use on own smoking is low. Majority of Serbian adults think e-cigarette should be regulated as a tobacco product.